Analysis of the Access of the Brazilian Population to Basic Sanitation Services (Research, Society and Development, 2019)
Basic sanitation corresponds to the set of public drinking water supply services, collection, treatment and adequate final disposal of sanitary sewage, drainage and management of urban rainwater, besides urban cleaning and solid waste management is governed by Federal Law 11.445 / 07 (Federal Basic Sanitation Law). The World Health Organization (WHO) defines sanitation as a control of physical factors that can cause harmful effects on the human being, be it physical, mental or social well-being. The objective of this study is to present a context about the topic of legislation in Brazil, as well as theories addressed by researchers in order to better discuss and understand the theme. Thus, we sought to demonstrate and present the Brazilian reality through the deductive method and the documentary and bibliographic research technique, based on data collected by the Brazilian Institute of Geography and Statistics (IBGE), in its National Household Sample Survey ( PNAD), carried out in the period from 2005 to 2015, in which there was a need for Management focused on the problem, given the presentation of alarming numbers.